Chemical Assessment of Ballast Water Exchange Compliance: Implementation in North America and New Zealand - Noble, Monaca; Ruiz, Gregory M.; Murphy, Kathleen R. (Frontiers in Marine Science, 2016)
Fluorescence by naturally occurring dissolved organic matter (FDOM) is a sensitive indicator of ballast water source, with high FDOM in coastal ballast water decreasing typically dramatically when replaced by oceanic seawater during ballast water exchange. In this study, FDOM was measured in 92 ships arriving at Pacific ports on the US west coast and in New Zealand, and used to assess their compliance with ballast water regulations that required 95% replacement of port water to minimize invasive species risks. Fluorescence in many ships that reported ballast water exchange was significantly higher than is usual for oceanic seawater, and in several cases, significantly higher than in other ships with similar provenance and ballast water management. Pre-exchange source port conditions represented the largest source of uncertainty in the analysis, because residual coastal FDOM when highly fluorescent can significantly influence the fluorescence signature of exchanged ballast water. A meta-analysis comparing the intensities of FDOM in un-exchanged ballast tanks with calculated pre-exchange intensities assuming that ships all correctly implemented and reported ballast water exchange revealed notable discrepancies. Thus, the incidence of high-FDOM port waters was seven times lower in reality than would be expected on the basis of these calculations. The results suggest that a significant rate of reporting errors occur due to a combination of factors that may include inadequate ballast water exchange and unintentional or deliberate misreporting of ballast water management.